2012
DOI: 10.1100/2012/916705
|View full text |Cite
|
Sign up to set email alerts
|

Current Status of Trace Metal Pollution in Soils Affected by Industrial Activities

Abstract: There is a growing public concern over the potential accumulation of heavy metals in soil, owing to rapid industrial development. In an effort to describe the status of the pollutions of soil by industrial activities, relevant data sets reported by many studies were surveyed and reviewed. The results of our analysis indicate that soils were polluted most significantly by metals such as lead, zinc, copper, and cadmium. If the dominant species are evaluated by the highest mean concentration observed for differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
57
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(61 citation statements)
references
References 76 publications
0
57
0
4
Order By: Relevance
“…On the other hand, excess iron may also interfere with components of the copper homeostasis and sensitize the bacteria to copper toxicity under anaerobic conditions (5). Since polluted water often contains different toxic metals (3,4), the interplay between copper and iron/iron-sulfur clusters in microorganisms will require further investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, excess iron may also interfere with components of the copper homeostasis and sensitize the bacteria to copper toxicity under anaerobic conditions (5). Since polluted water often contains different toxic metals (3,4), the interplay between copper and iron/iron-sulfur clusters in microorganisms will require further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…In U.S. groundwater, copper concentrations range from undetectable to approximately 1 mM, with most samples in the nanomolar range (3). In industrial and mining waste streams, micromolar to millimolar concentrations of copper have also been found (4). Copper at high concentrations in water has become a threat to all living organisms (5).…”
mentioning
confidence: 99%
“…A survey of public testing data showed that copper levels in U.S. groundwater range from undetectable to approximately 1 mM, with most samples in the nanomolar range (9). Micro-to millimolar concentrations, which represent the high end of the range, are found particularly in industrial and mining waste streams (10,11). There are several mechanisms by which copper is toxic (6,12,13).…”
mentioning
confidence: 99%
“…68 Bhaluka industrial area in Mymensingh was infested with various textiles and garment industries. Textile industries soils contain high levels of lead than in textile effluents in Bangladesh [84]. [85].…”
Section: Heavy Metal Pollution Of City Areamentioning
confidence: 99%